Clinical Trials of Immunogene Therapy for Spontaneous Tumors in Companion Animals - Gerardo Claudio Glikin; Liliana María Elena Finocchiaro (The Scientific World Journal)
Despite the important progress obtained in the treatment of some pets’ malignancies, new treatments need to be developed. Being critical in cancer control and progression, the immune system’s appropriate modulation may provide effective therapeutic options. In this review we summarize the outcomes of published immunogene therapy veterinary clinical trials reported by many research centers. A variety of tumors such as canine melanoma, soft tissue sarcomas, osteosarcoma and lymphoma, feline fibrosarcoma, and equine melanoma were subjected to different treatment approaches. Both viral and mainly nonviral vectors were used to deliver gene products as cytokines, xenogeneic tumor associated antigens, specific ligands, and proapoptotic regulatory factors. In some cases autologous, allogenic, or xenogeneic transgenic cytokine producing cells were assayed. In general terms, minor or no adverse collateral effects appeared during this kind of therapies and treated patients usually displayed a better course of the disease (longer survival, delayed or suppressed recurrence or metastatic spread, and improvement of the quality of life). This suggests the utility of these methodologies as standard adjuvant treatments. The encouraging outcomes obtained in companion animals support their ready application in veterinary clinical oncology and serve as preclinical proof of concept and safety assay for future human gene therapy trials.